Inflammatory and Cell-Mediated Immune Responses in the Respiratory Tract of Chickens to Infection with Avian Infectious Bronchitis Virus - Okino, Cintia Hiromi [UNESP]; Santos, Igor Leonardo dos [UNESP]; Fernando, Filipe Santos [UNESP]; Alessi, Antonio Carlos [UNESP]; Wang, Xiuqing; Montassier, Helio Jose [UNESP] (Mary Ann Liebert, Inc, 2014)
Tracheal mucosa is the primary site of replication of avian infectious bronchitis virus (IBV), which leads to both morphologic and immune modulatory changes in this organ. To increase the understanding of the mechanisms involved in these processes, we focused on the evaluation of local inflammatory and cell-mediated immune responses after challenge with the M41 strain of IBV, associating these responses with pathologic changes in the tracheal mucosa. At 24 h post-infection, inflammatory cytokines related genes were significantly upregulated, including peaks of TNFSF15 and TGF beta mRNA production, although no tracheal microscopic alterations were observed and only a slightly increase in viral load occurred. At 3 days post-infection (dpi), we observed that the highest upregulation of IL6, IL1 beta, and IFN gamma coincided with highest scores of viral load and microscopic lesions, suggesting a role of both these cytokines and virus load on the development of tracheal lesions. Later, at 7 dpi, the most prominent increases of CD8 alpha alpha mRNA and Granzyme homolog A mRNA were followed by a significant decrease of scores of tracheal lesions and viral load. In conclusion, an early upregulation of expression of proinflammatory cytokines such as IL6, IL1 beta, and IFN gamma induced by the M41 strain of IBV may be partially implicated in the viral pathogenicity on trachea tissues of nonimmune challenged chickens, in addition to a late induction of a putative protective immune responses by this virus through upregulation of CD8 alpha alpha and Granzyme homolog A genes in this organ.